The rights of detainee under Internal Security Act 1960 / Noor Hidayah Azhar, Fazrina Mohd Faruk and Shazleen Said - Azhar, Noor Hidayah; Faruk, Fazrina Mohd; Said, Shazleen (2009)
Based on our observations from decided cases, references to some articles on the net and a further library study made, we found that there is a need to come out with a study regarding this issue. There are some rights that were denied on the detainees, which is the right that was provided under Article 5(3) and 5(4) of Federal Constitution. Our studies seek to examine why the rights of detainees to recourse for a fair trial and to seek for the assistance of legal representative have been denied. We also aim to identify the scope and limitation of Article 5(3) and 5(4) of Federal Constitution particularly in the position of detainees arrested under Internal Security Act. We also like to identify whether there is any need for the Internal Security Act to be repealed so that it will be in accordance with our Constitution. We conducted several interview such as with a Registrar, a law lecturer and with representative from non-governmental body such as Suara Rakyat Malaysia (SUARAM) to enhance our understanding and gain more knowledge. Finally, we included some suggestion and recommendations provided by our interviewer and from our own perspective view while conducting this research.